PENGARUH TERAPI KOMPRES HANGAT TERHADAP NYERI HAID (DISMENOREA) PADA SISWI SMK PERBANKAN SIMPANG HARU PADANG - Dahlan, Asmita; Syahminan, Tri Veni (Jurnal Ipteks Terapan, 2016)
Abdominal muscle contractions that occur continuously due to the release of menstrual blood causes the pain of dysmenorrhea. The prevalence of dysmenorrhea is very high, about 50% of young women. In Indonesia the incidence of dysmenorrhea is composed of 54.89% and 9.36% of primary dysmenorrhoea secondary dysmenorrhoea. Many teens who do not attend school because of dysmenorrhoea. Giving a warm compress will dilate blood vessels thereby increasing local blood flow resulting in relaxation then can reduce pain. This type of research pre-eksprerimen one goup pre-post test. The data collection was conducted in April â Mei 2015. The population in this study SMK Simpang Haru Banking Padang experiencing dysmenorrhoea. The sample of 16 respondents pengambilan by purposive sampling technique. Data were analyzed using paired t-test. The results showed that the average pain respondent before being given a warm compress is 5.60 with a standard deviation of 1,549, the average pain responder after being given a warm compress is 2.62 with a standard deviation of 1,204, there is a significant difference before and after a warm compress with p = 0.000 where p <0.05. Warm compresses can reduce pain dysmenorrhoea at SMK Simpang Haru Banking Padang. It is therefore recommended to health care compress